Comprehensive Energy Management - Eco Routing & Velocity Profiles - Watzenig, Daniel; Brandstätter, Bernhard; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
The book discusses the emerging topic of comprehensive energy management in electric vehicles from the viewpoint of academia and from the industrial perspective. It provides a seamless coverage of all relevant systems and control algorithms for comprehensive energy management, their integration on a multi-core system and their reliability assurance (validation and test). Relevant European projects contributing to the evolvement of comprehensive energy management in fully electric vehicles are also included.
Introduction -- Aspects for Velocity Profile Optimization for Fleet Operated Vehicles -- Semi-Autonomous Driving Based on Optimized Speed Profile -- The Design of Vehicle Speed Profile for Semi-Autonomous Driving -- Energy Efficient Driving in Dynamic Environment: Considering Other Traffic Participants and Overtaking Possibility -- Model-Based Eco-Routing Strategy for Electric Vehicles in Large Urban Networks.
Keywords: Automotive engineering; Energy policy; Energy and state; Control engineering; Automotive Engineering; Energy Policy, Economics and Management; Control and Systems Theory